The Influence of Hijab Fashion Trends on Consumptive Behavior of Students of the Faculty of Islamic Economics and Business UIN K. H. Abdurrahman Wahid Pekalongan - Iiq Nahyu Risqiawati; Hendri Hermawan; Muhammad Shulthoni (Journal of Noesantara Islamic Studies, 2024)
The hijab is not a piece of jewelry and is not worn to gain popularity. Therefore, some women who wear the hijab here choose to wear it in different styles. If there is a new hijab style, some women will follow it and wear the hijab to study or work. There is nothing wrong with wearing the hijab according to fashion, but if you force it too much (when buying), it is not recommended in Islam. The hijab fashion trend followed by FEBI UIN KH students. Based on interviews, Abdurrahman Wahid Pekalongan greatly influenced his consumer behavior because he could express himself. This research aims to investigate and analyze how hijab fashion influences the consumption behavior of UIN KH Abdurrahman Wahid Pekalongan students. Data collection methods in this research are observation and interviews. The data sources used are primary data sources and secondary data sources. Data analysis uses a quantitative descriptive approach. The results of this study indicate that the use of fashionable hijab among female students of the Faculty of Economics and Islamic Business has become a trend and influences their consumptive behavior, as evidenced by the comfort they feel when using fashionable hijab and adding to their self-confidence.